RANCANGAN SISTEM INFORMASI PEMBELIAN DAN PENJUALAN PADA TOKO CITRA COMPUTER JAKARTA BARAT - hizkia imanuel; Wahyu Tisno Atmojo (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The very rapid progress of science and technology is increasingly encouraging humans to improve and even create a new technology that is beneficial to humans. One proof of technological progress is the computer. Not all businesses have used a computerized system, one of which is the West Jakarta computer image. Based on this background, it can be formulated, namely How to build a purchasing and sales information system at the West Jakarta computer image store. The data collection method used to make this database application is the method of interview, observation and literature study. For system development in this study using the waterfall method. In this application using the “Microsoft Visual Basic.NET” programming language. The results of this study in the form of “Purchase and Sales Information Systems at the Citra Computer Store West Jakarta”. This database application was recommended and created using “Visual Basic 2008” and “SQL Server 2005”.